Pengaruh Latihan Plyometric terhadap Kecepatan Memanjat pada Atlet Speed World Record Panjat Tebing Bungo - Monica Pratama Putri; Ikhsan Maulana Putra; Desi Tri Susanti (CV. Master Literasi Indonesia, 2025)
The aim of this study was to determine the effect of plyometric training on climbing speed in a world-record-holding rock climber in Bungo Regency. This research is quantitative and uses a quasi-experimental method with a single-group pretest-posttest design. The study population was 15 athletes, using a propositional sampling technique. The sample size was 12 male athletes. The study was conducted over 16 meetings. The instrument used in this study was a speed test to break the world speed record. The exercises provided included hurdle jumps and single-leg jumps. Based on the results of the t-test analysis of climbing speed in Bungo rock climbing speed world record athletes with plyometric training in the form of hurdle hop and single leg jump training, the calculated t value (5.27) > t table (1.79) was obtained. Thus, it can be concluded that there is an effect of plyometric training on climbing speed in Bungo rock climbing speed world record athletes.